Paradoxical cardiac conduction during exercise stress testing in myotonic dystrophy type 1: a case report. Issue 11 (12th October 2021) - Ahmad, Suliman; Kabunga, Peter
Abstract: Background : Exercise stress testing (EST) identifies functional abnormalities that may manifest only during physiologic stress to the heart. This may have significant prognostic value in identifying latent conduction abnormalities in asymptomatic patients with myotonic dystrophy type 1 (MD1), who may benefit from prophylactic permanent pacemaker (PPM) implantation. Case report : We report the case of a patient with MD1 with a 5-month history of atypical left-sided chest pain. Her baseline electrocardiogram (ECG) showed sinus rhythm and variable PR interval prolongation (206–220 ms) without symptoms of cardiac conduction disease. Routine blood tests and cardiac investigations including a 24-h ECG monitoring, echocardiogram, and a cardiac magnetic resonance imaging scan, revealed no abnormalities. To investigate her chest pain and to determine the need for prophylactic PPM implantation, EST and an electrophysiological study were performed. Exercise testing revealed minimal PR shortening (PR = 200 ms) at peak exercise and paradoxical PR prolongation (PR = 280 ms) during the early recovery period. A prophylactic DDDR PPM was implanted following an electrophysiological study that revealed a prolonged His-ventricle (HV) interval of 84 ms. Discussion : The current use of annual ECG and 24 Holter monitoring may not adequately detect abnormal cardiac conduction in asymptomatic patients with MD1. The invasive nature of electrophysiology studies limits its use as a screening tool for conduction abnormalities in asymptomatic patients. Thus, EST could be used to identify underlying conduction abnormalities in MD1 patients without any specific symptoms of bradycardia, which warrant further invasive electrophysiological studies (EPS).